INTERPRETIVE SUBJECTIVATION ANALYSIS – A CRITICAL PERSPECTIVE ON THE DISCURSIVE SITUATEDNESS OF HUMAN SUBJECTIVITIES - BOSANČIĆ, SAŠA (Society Register, 2019)
One of the developments based on the approach of Berger and Luckmann focuses on the analysis of discourses and subjectivation processes. The Interpretive Subjectivation Analysis (ISA) takes up these developments in order to establish a research perspective on the decentered subject that combines the theories of the Interpretive Paradigm of Sociology and the post-structuralist concepts of subjectivation as established in Judith Butler’s and Michel Foucault’s work. This paper outlines a qualitative methodological framework to analyze processes of subjectivation by including and relating empirical data on different levels. In order to show how this type of research can broaden the perspective on human subjectivities, the article discusses different empirical studies that focus on questions of inequality and marginalization.